Natural History of Histopathologic Changes in Cardiomyopathy of Golden Retriever Muscular Dystrophy - Schneider, Sarah M.; Sansom, Garett T.; Guo, Lee-Jae; Furuya, Shinji; Weeks, Brad R.; Kornegay, Joe N. (Frontiers in Veterinary Science, 2022)
Background Duchenne muscular dystrophy (DMD) is an X-linked inherited myopathy that causes progressive skeletal and cardiac muscle disease. Heart lesions were described in the earliest DMD reports, and cardiomyopathy is now the leading cause of death. However, diagnostics and treatment for cardiomyopathy have lagged behind those for appendicular and respiratory skeletal muscle disease. Most animal model studies have been done in the mdx mouse, which has a relatively mild form of cardiomyopathy. Dogs with the genetically homologous condition, Golden Retriever muscular dystrophy (GRMD), develop progressive cardiomyopathy analogous to that seen in DMD. Previous descriptive studies of GRMD cardiomyopathy have mostly been limited to selective sampling of the hearts from young dogs. Methods and Results We systematically assessed cardiac lesions in 31 GRMD and carrier dogs aged 3 to 76 months and a separate cohort of 2–10-year-old normal hounds. Both semi-quantitative lesion scoring and quantitation of the cross-sectional area of fibrosis distinguished dogs with GRMD disease from normal dogs. The carriers generally had intermediate involvement but had even greater fibrosis than GRMD dogs. Fatty infiltration was the most prominent feature in some older GRMD dogs. Vascular hypertrophy was increased in GRMD dogs and correlated positively with lesion severity. Purkinje fiber vacuolation was also increased but did not correlate with lesion severity. Histopathologic changes correlated with late gadolinium enhancement on cardiac MRI. Conclusion These features are generally compatible with those of DMD and further validate GRMD as a useful model to study cardiomyopathy pathogenesis and treatment. Additionally, the nature of some degenerative lesions suggests that functional hypoxia or non-thrombotic ischemia may contribute to disease progression.